THE ROLE OF BENGKULU REGIONAL SUPERVISION INSPECTORATE IN PREVENTING TAX FRAUD AT POLDA BENGKULU ENVIRONMENT - Rusli Rachman; Lidia Br Karo; Herlambang Herlambang (Universitas Bengkulu, 2020)
Tax fraud is a behavior that is not justified by law, but in Regional Police (Polda) of Bengkulu the behavior is often found by the supervisory apparatus in 2019 with a total loss that has been deposited of Rp 57,668,922. In order to minimize and eliminate these behaviors, efforts and sanctions were required by the supervisory apparatus carried out by Itwasda (Regional Inspectorate Supervision) Polda Bengkulu. From this background, the problemsexamined were: (1) What was the role of the Itwasda Polda Bengkulu in preventing Tax Fraud within Polda Bengkulu? (2) What was the form of sanctions imposed by Itwasda Polda Bengkulu in responding to the work unit that embezzled tax money? To answer these problems, this study used descriptive research method. The type of this research was an empirical research. The sources data used were primary and secondary data. The processing data was done by editing, coding, reconstructing, systematizing then analyzing qualitatively using the deductive-inductive and inductive-deductive methods. The results showed that (1) Preventive Field was held based on the number of findings related to tax fraud in 2019 and has been running quite well and effectively. In addition, Itwasda Bengkulu has also made innovations in the form of activities such as Prawasrik (Pre Supervision and investigation), Verification Team of Perwabkeu (Financial Accountabilty) and Internal Coordination improvement (2) Repressive Field was in the form of Wasrik activities by providing findings along with recommendations on the object of inspection. The result concluded that the number of findings in the field of taxation and deprivasion was increasingly reduced.